Analisis Dampak Serangan Black Hole terhadap Kinerja Protokol AODV dan DYMO pada MANET (Mobile Ad-Hoc Network) - I Putu Krisna Yoga Tanaya; Rakhmadhany Primananda; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Ad-Hoc Network (MANET) is a set of mobile devices that communicates with each other over wireless networks without a centralized or structured network. MANET has three types of routing protocols, it named proactive routing protocol, reactive routing protocol, and hybrid routing protocol. One particular characteristic of MANET, which is security limitations, causes security to be a weakness in MANET so that attacks on MANET can cause a decrease in performance in the routing protocol. Based on these problems, the authors made a study entitled Analysis Impact of Black Hole Attacks on the Performance of AODV and DYMO Protocols on MANET (Mobile Ad-Hoc Network). The result in this study is black hole attacks affected the performance of the AODV protocol and the DYMO protocol. Tests are carried out using network simulator-2 (NS-2) with three test scenarios, those are a density of 40, 60, and 80 nodes with variations in the number of attack nodes (black holes). Variation in the number of attack nodes (black holes) as many as 5, 10, 15, and 20. Performance parameters that used in this test is including the packet of delivery ratio, normalized routing load, and packet loss. The results of the study show that the packet delivery ratio on the DYMO protocol is better than the AODV protocol with an average overall PDR result in the AODV protocol of 34,2%. While the DYMO protocol is 42,1%.